Mapping Gaps in Sugarcane Fields Using UAV-RTK Platform - Oliveira, Matheus Pereira de [UNESP]; Cardoso, Paulo Henrique [UNESP]; Oliveira, Romário Porto de [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; da Silva, Rouverson Pereira [UNESP] (MDPI, 2023)
Unmanned aerial vehicles (UAVs) equipped with a global real-time kinematic navigation satellite system (GNSS RTK) could be a state-of-the-art solution to measuring gaps in sugarcane fields and enable site-specific management. Recent studies recommend the use of UAVs to map these gaps. However, low-accuracy GNSS provides incomplete or inaccurate photogrammetric reconstructions, which could easily generate an error in the gap measurement and constrain the applicability of these techniques. Therefore, in this study, we evaluated the potential of UAV RTK imagery for mapping gaps in sugarcane. To compare this solution with conventional UAV approaches, the precision and accuracy of RTK and non-RTK flights were evaluated. To increase the robustness of the research, flights were performed to map gaps found naturally in the field and with plants at different stages of development. Our results showed that the lengths of gaps identified by both RTK and non-RTK UAV imagery were similar, with differences in precision and accuracy of about 1% for both systems. In contrast, RTK was much more efficient and provides stakeholders with guidelines for accurate and precise mapping gaps, allowing them to make confident decisions on site-specific management.
Keywords: plant height; positional accuracy; site-specific management; sugarcane gaps; UAV-RTK